Correspondence and American literature, 1770-1865 - Hewitt, Elizabeth 1965- (Cambridge studies in American literature and culture, 2004)
Elizabeth Hewitt uncovers the centrality of letter-writing to antebellum American literature. She argues that many canonical American authors turned to the epistolary form as an idealised genre through which to consider the challenges of American democracy before the Civil War. The letter was the vital technology of social intercourse in the nineteenth century and was adopted as an exemplary genre in which authors from Crevecoeur and Adams through Jefferson, to Emerson, Melville, Dickinson and Whitman, could theorise the social and political themes that were so crucial to their respective literary projects. They interrogated the political possibilities of social intercourse through the practice and analysis of correspondence. Hewitt argues that although correspondence is generally only conceived as a biographical archive, it must instead be understood as a significant genre through which these early authors made sense of social and political relations in the nation